CHECKLIST OF TERMITE (ISOPTERA) RECORDED FROM BUKIT LAWANG, NORTH SUMATRA - Syaukani Syaukani (Universitas Syiah Kuala, 2012)
A survey was conducted to explore species richness of termite at Bukit Lawang (North Sumatra) in 2012. Termites were sampled by adopting a standardized smpling protocol (Belt Transects) at different altitudes (150m, 250m, 350m). As many as 30 species and three families (Kolotermitidae, Termitidae) were collected. None of the species under Kalotermitidae collected from the field were probably related to the limited area surveyed and nesting behaviour (which generally inhabitant into dead branches and twigs)